2008
DOI: 10.1128/jb.00481-08
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Phenylacetic Acid Catabolic Pathway Is Required for Full Pathogenicity of Burkholderia cenocepacia in the Caenorhabditis elegans Host Model

Abstract: Burkholderia cenocepacia is a member of the Burkholderia cepacia complex, a group of metabolically versatile bacteria that have emerged as opportunistic pathogens in cystic fibrosis and immunocompromised patients. Previously a screen of transposon mutants in a rat pulmonary infection model identified an attenuated mutant with an insertion in paaE, a gene related to the phenylacetic acid (PA) catabolic pathway. In this study, we characterized gene clusters involved in the PA degradation pathway of B. cenocepaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
77
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 53 publications
5
77
0
7
Order By: Relevance
“…S1, step 15 and 18), and BCAL0407 as a homolog of PP_3280, the putatively identified paaJ gene of P. putida KT2440 by our bi-directional BLASTP search. This corroborates our previous annotation where BCAM2568 and BCAL0407 were both identified as candidate paaJ genes (Law et al 2008). …”
Section: Computational Analysis Of the Phenylalanine Catabolic Pathwasupporting
confidence: 79%
See 1 more Smart Citation
“…S1, step 15 and 18), and BCAL0407 as a homolog of PP_3280, the putatively identified paaJ gene of P. putida KT2440 by our bi-directional BLASTP search. This corroborates our previous annotation where BCAM2568 and BCAL0407 were both identified as candidate paaJ genes (Law et al 2008). …”
Section: Computational Analysis Of the Phenylalanine Catabolic Pathwasupporting
confidence: 79%
“…cenocepacia J2315 (Law et al 2008). However, our bidirectional BLASTP search identified BCAS0364 as the best hit to b1387 (paaZ) from E. coli K-12 MG1655 ( Fig.…”
Section: Computational Analysis Of the Phenylalanine Catabolic Pathwamentioning
confidence: 99%
“…Another pathway highly induced under CF conditions is involved in phenylacetate (Paa, a byproduct of aromatic catabolism) metabolism although Paa was not detectable in our medium before growth so the reason for this induction is not obvious. However, it was recently shown that mutations in this pathway disrupted Burkholderia virulence in a C. elegans model system (9). Members of the general secretion (Sec) pathway were also induced under CF conditions.…”
Section: Resultsmentioning
confidence: 99%
“…As such, the initial enzyme of the PAA pathway, phenylacetateCoA ligase (PCL), plays a vital role in regulating entry of potential substrates into the pathway. An unusual feature of the PAA pathway in B. cenocepacia is that it encodes two copies of the pcl gene (paaK1 and paaK2), yet harbors only a single copy of each subsequent enzyme in the pathway (2). Although a rationale for the additional PCL in B. cenocepacia has not been established, studies of related bacterial PCLs suggest the potential for altered kinetics (6 -8).…”
mentioning
confidence: 99%
“…For example, the degradation of phenylacetic acid (PAA) 3 is proposed to facilitate B. cenocepacia in establishing lifethreatening infections in cystic fibrosis patients (1). Although the precise mechanism that governs this process is not yet understood, it is speculated that early PAA degradation pathway intermediates play a role in host cell damage (2,3).…”
mentioning
confidence: 99%